2022
DOI: 10.1101/2022.02.14.480363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic Surveillance of Salmonella spp. in the Philippines, 2013-2014

Abstract: Increasing antimicrobial resistance (AMR) in Salmonella has been observed in the Philippines. This study aims to utilize whole genome sequencing (WGS) to characterize the population and AMR mechanisms of Salmonella captured by the Philippine Antimicrobial Resistance Surveillance Program (ARSP) and contrast to traditional laboratory methods. We sequenced the whole genomes of 148 SalmonellaTyphi (S. Typhi) and 65 non-typhoidal Salmonella (NTS) collected in the Philippines in 2013-2014. From the genome sequences,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…Salmonella studies with confirmed serovar identification are limited to clinical samples from the Philippine Department of Health − Antimicrobial Resistance Surveillance Program (DOH-ARSP) of the RITM. In a surveillance study covering blood and stool samples obtained from 17 sentinel sites all over the country from 2013 to 2014, in silico genotyping using WGS revealed that the most dominant serovars were S. Typhi as well as S. Enteritidis and ST34 (I 4, [5],12: i: -) for the non-typhoidal types (Lagrada et al, 2022).…”
Section: Serovarsmentioning
confidence: 99%
“…Salmonella studies with confirmed serovar identification are limited to clinical samples from the Philippine Department of Health − Antimicrobial Resistance Surveillance Program (DOH-ARSP) of the RITM. In a surveillance study covering blood and stool samples obtained from 17 sentinel sites all over the country from 2013 to 2014, in silico genotyping using WGS revealed that the most dominant serovars were S. Typhi as well as S. Enteritidis and ST34 (I 4, [5],12: i: -) for the non-typhoidal types (Lagrada et al, 2022).…”
Section: Serovarsmentioning
confidence: 99%